Behavior Change for Early Childhood Nutrition: Effectiveness of Health Worker Training Depends on Maternal Information in a Randomized Control Trial - Prakarsh Singh; William A. Masters (Institute for the Study of Labor (IZA), 2016)
We carry out a randomized control trial to test for interaction effects between training state-employed caregivers and providing mothers information to improve nutrition of preschool children aged 2-6 in rural India. Salaried caregivers are supposed to provide a mid-day meal and also advise mothers on health and nutrition for their child. Our one-day caregiver training covered basic health and nutrition facts with advice on how to communicate with mothers for behavior change at home. We find that this training was effective only when we provided the mothers with an independent source of nutrition information, and that the combined treatment was effective only among younger caregivers. Results are consistent with behavior change as a costly investment that is more attractive when done earlier in life, and greater response to information that is confirmed and reinforced from multiple sources.
Keywords: M53; I12; I38; J38; 330; child underweight; child malnutrition; child health; ICDS; Punjab; South Asia